A Polish Sourcebook on the Living Dead - Džekčioriūtė, Vita (Tautosakos darbai, 2024)
Łukasz Kozak, With Stake and Spade. Vampiric Diversity in Poland. An Introduction and Sourcebook, translated by Mark Bence, Warsaw: Adam Mickiewicz Institute, Evviva L’arte Foundation, 2020, 179 p., ISBN 978-83-60263-60-0, ISBN 978-83-956895-4-3